2021
DOI: 10.1111/opn.12442
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care plans in long‐term care facilities for the older persons—How well is information from RAI assessments utilised in care planning?

Abstract: Background: In Finland, care plans at long-term care facilities (LTCF) for the older persons should be based on information from Resident Assessment Instrument (RAI) assessments and the principles of structured data. Hence, managers are responsible for ensuring that the RAI system is used to a satisfactory extent, the provided information is used in care planning, and that staff members are competent at composing high-quality care plans. Aim:To explore the congruence between first-line managers' assessments of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Their crucial role in implementation has also been underscored in previous studies (Meza et al., 2021; Williams et al., 2020). However, other Finnish studies revealed some deficiencies in frontline leaders' RAI competencies (Kuha et al., 2022; Niemelä et al., 2018). As noted in both this study and Toye' (2016), these deficiencies may hinder the instrument's implementation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Their crucial role in implementation has also been underscored in previous studies (Meza et al., 2021; Williams et al., 2020). However, other Finnish studies revealed some deficiencies in frontline leaders' RAI competencies (Kuha et al., 2022; Niemelä et al., 2018). As noted in both this study and Toye' (2016), these deficiencies may hinder the instrument's implementation.…”
Section: Discussionmentioning
confidence: 95%
“…Conversely, a lack of leader participation (de Stampa et al., 2018), knowledge, understanding and support has been found to hinder its implementation (Toye, 2016). However, deficiencies have been found in professionals' and leaders' RAI competencies in Finland (Kuha et al., 2022; Niemelä et al., 2018).…”
Section: Introductionmentioning
confidence: 99%